MODEL CONTEXTUAL TEACHING AND LEARNING DAN PENGUATAN KONSERVASI BUDAYA BAGI MAHASISWA - Sunahrowi, Sunahrowi (Badan Pengembang Konservasi UNNES, 2016)
The course Introduction to Cultural Studies at the Faculty of Languages and Arts, Universitas Negeri Semarang also should be one of the steps to prepare as best generation aspired Education Law. Semarang Universitas Negeri Semarang as a university conservation where one of the goals of conservation is the conservation of cultural pre-requisites to make very interesting if we (researchers) as an integral part of the university made its contribution. Innovation introductory science teaching material culture with contextual teaching and learning method is expected to be the answer to all the questions and confusion students about cultural sciences introductory books that are too difficult to understand because many theoretical. In fundamental teaching material Introduction to Cultural Studies is divided into five parts, among others; (1) Culture , (2) Modernism, (3) Postmodernism, (4) Feminism, and (5) Orientalism.Â Mata kuliah Pengantar Ilmu Budaya di Fakultas Bahasa dan Seni Universitas Negeri Semarang juga hendaknya menjadi salah satu langkah mempersiapkan generasi terbaik sebagaimana yang dicita-citakan UU Sisdiknas. Universitas Negeri Semarang sebagai universitas konservasi di mana salah satu tujuan konservasi adalah konservasi budaya menjadikan pra-syarat yang sangat menarik apabila kita (peneliti) sebagai bagian integral dari universitas memberikan sumbangsihnya. Inovasi bahan ajar pengantar ilmu budaya dengan metode contextual teaching and learning ini diharapkan menjadi jawaban atas segala pertanyaan dan kebingunan mahasiswa mengenai buku pengantar ilmu budaya yang terlalu sulit untuk dipahami karena banyak yang bersifat teoritis. Secara mendasar materi ajar Pengantar Ilmu Budaya terbagi menjadi lima bagian, antara lain ; (1) Budaya dan Kebudayaan, (2) Modernisme, (3) Posmodernisme, (4) Feminisme, dan (5) Orientalisme.Â